Numerical Analysis of Optical Properties Using Octagonal Shaped Ge15As15Se17Te53 Chalcogenide Photonic Crystal Fiber - Thuy, Nguyen Thi (VNU Journal of Science: Mathematics - Physics; Vol 40 No 2DO - 10.25073/2588-1124/vnumap.4873, 2024)
A novel Ge 15 As 15 Se 17 Te 53 chalcogenide-based photonic crystal fiber with octagonal cladding was designed which exhibits low confinement loss and high nonlinearity. The dispersion properties were investigated over a wide wavelength range of up to 11 µm. Based on preliminary simulation results, three fibers with suitable characteristic quantities are proposed for supercontinuum generation. Among these fibers, fiber #F 1 ( Ʌ = 3.1 µm, d/Ʌ = 0.3) exhibits all-normal dispersion with a small value of −0.374 ps/[nm.km]. At the same time, the highest nonlinear coefficient of 2876.861 W −1 .km −1 at the pump wavelength of 5.45 µm is also found. The #F 2 fiber ( Ʌ = 4.5 µm, d/Ʌ = 0.3) has anomalous flat dispersion with one zero dispersion wavelength. This fiber has the smallest dispersion and lowest confinement loss values of 0.281 ps/[nm.km] and 1.360×10 −9 at 5.7 µm pump wavelength, respectively. With the anomalous dispersion, #F 3 fiber ( Ʌ = 3.5 µm, d/Ʌ = 0.3) offers a small effective mode area of 20.892 µm 2 and a low confinement loss of 4.974×10 −8 dB/m at 5.25 µm wavelength. The proposed fibers can possess a low peak power, broadband supercontinuum source, suitable for application fields such as optical communication and biomedical sensors.